Conflict and community in Corinth : a socio-rhetorical commentary on 1 and 2 Corinthians - Witherington, Ben, III, 1951- (W.B. Eerdmans ; Paternoster Press, 1995)
This commentary applies an exegetical method informed by both sociological insight and rhetorical analysis to the study of I and 2 Corinthians. The study also analyzes the two letters of Paul in terms of Greco-Roman rhetoric and ancient social conditions and customs to shed fresh light on the context and content of the message.